2013
DOI: 10.1073/pnas.1219997110
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial TLR4 activation impairs intestinal microcirculatory perfusion in necrotizing enterocolitis via eNOS–NO–nitrite signaling

Abstract: Necrotizing enterocolitis (NEC) is a devastating disease of premature infants characterized by severe intestinal necrosis and for which breast milk represents the most effective protective strategy. Previous studies have revealed a critical role for the lipopolysaccharide receptor toll-like receptor 4 (TLR4) in NEC development through its induction of mucosal injury, yet the reasons for which intestinal ischemia in NEC occurs in the first place remain unknown. We hypothesize that TLR4 signaling within the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(192 citation statements)
references
References 25 publications
12
177
1
2
Order By: Relevance
“…Recent studies have highlighted such differences, such as those showing that intraepithelial T cell receptor γδ lymphocytes are decreased in surgical NEC specimens compared with appropriate controls [55], as are lamina propria T regulatory cells [56]. A key player in intestinal inflammation and the response to pathogens is TLR4, and recent work has shown that TLR4 signalling is important in the development of NEC [33,57,58,59]. Intriguingly, TLR4 signalling also links to other factors involved in the pathogenesis of NEC, such as the microcirculation [59] (see below).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted such differences, such as those showing that intraepithelial T cell receptor γδ lymphocytes are decreased in surgical NEC specimens compared with appropriate controls [55], as are lamina propria T regulatory cells [56]. A key player in intestinal inflammation and the response to pathogens is TLR4, and recent work has shown that TLR4 signalling is important in the development of NEC [33,57,58,59]. Intriguingly, TLR4 signalling also links to other factors involved in the pathogenesis of NEC, such as the microcirculation [59] (see below).…”
Section: Pathogenesismentioning
confidence: 99%
“…A key player in intestinal inflammation and the response to pathogens is TLR4, and recent work has shown that TLR4 signalling is important in the development of NEC [33,57,58,59]. Intriguingly, TLR4 signalling also links to other factors involved in the pathogenesis of NEC, such as the microcirculation [59] (see below).…”
Section: Pathogenesismentioning
confidence: 99%
“…LPS signaling activates leukocytes and vascular endothelial cells, leading to up-regulation of adhesion molecule expression and function, promoting adhesion of leukocytes to endothelial cells (Kim et al, 2011;Yazji et al, 2013;. Activation of leukocytes and endothelial cells also up-regulates production of pro-inflammatory cytokines (Zhang et al, 2011), resulting in recruitment of more leukocytes to sites of infection Therefore, LPS and TLR4 play a major role in the pathogenesis of sepsis-induced multiple organ dysfunction and death.…”
Section: Discussionmentioning
confidence: 99%
“…In the premature birth situation, intestinal TLR4 levels remain elevated and activation of TLR4 on the lining of the premature intestine by the Gram negative bacteria that colonize the premature gut leads to a number of deleterious effects, including increased enterocyte apoptosis, impaired mucosal healing and enhanced proinflammatory cytokine release, which in aggregate lead to the development of NEC [14] [15]. Also, the translocation of Gram-negative bacteria through the gut mucosa leads to activation of TLR4 on the lining of the endothelium of the premature bowel mesentery, resulting in a reduction in blood flow and the development of intestinal ischaemia and necrosis [16]. This explanation for the pathogenesis of NEC termed as "the cross-switching hypothesis" partially explains the reasons for which the premature infant is at risk of NEC development and why the disease occurs upon bacterial colonization.…”
Section: Hyper-reactive State Of Premature Intestinementioning
confidence: 99%